Beckman IR-1 Spectrophotometer with glass lid (1942)
The IR-1 Spectrophotometer was developed by Beckman Instruments, Inc. in 1942 as a secret project for the United States' Office of Rubber Reserve for use in creating artificial rubber during World War II. The IR-1 was based on Robert Brattain's existing single-beam design.
Keywords: Scientific apparatus and instruments; Spectrophotometer; Infrared spectroscopy; Beckman Instruments, Inc.